2023
DOI: 10.3389/fenvs.2023.1130463
|View full text |Cite
|
Sign up to set email alerts
|

Environment education: A first step in solving plastic pollution

Abstract: Plastic pollution has been today’s most highly visible environmental problem in the world. How to responsibly manage plastic waste to control and eliminate plastic pollution has been a global challenge. We have begun to address these issues and developed some science-based solutions and emerging technologies. However, tackling such an intractable challenge requires systematic solutions except for science-based and technology-based ones. Environmental education, fostering plastic pollution prevention within soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…By providing individuals with knowledge about plastic pollution and waste management strategies, environmental education programs can empower citizens to make informed decisions and adopt environmentally friendly practices. This finding underscores the importance of incorporating environmental education initiatives into public policies and educational curricula to address plastic waste pollution effectively [16], [29].…”
Section: Impact Of Environmental Education On Plastic Waste Reductionmentioning
confidence: 72%
See 1 more Smart Citation
“…By providing individuals with knowledge about plastic pollution and waste management strategies, environmental education programs can empower citizens to make informed decisions and adopt environmentally friendly practices. This finding underscores the importance of incorporating environmental education initiatives into public policies and educational curricula to address plastic waste pollution effectively [16], [29].…”
Section: Impact Of Environmental Education On Plastic Waste Reductionmentioning
confidence: 72%
“…Environmental education plays an important role in raising awareness about plastic pollution and encouraging sustainable behavior among individuals and communities [16], [17]. By providing knowledge about the environmental impacts of plastic waste and promoting…”
Section: Awarenessmentioning
confidence: 99%
“…In addition to technological innovations, education and awareness campaigns are essential in reducing plastic waste and preventing pollution. One study found that increasing environmental awareness and education can reduce the amount of plastic waste generated by individuals (Liu et al, 2023). Governments and organizations can also implement policies and regulations to reduce plastic production and promote sustainable alternatives, such as banning single-use plastics or implementing extended producer responsibility programs (Knoblauch and Mederake, 2021).…”
Section: Control Measure Strategies To Mitigate Marine Plasticsmentioning
confidence: 99%
“…The involvement of local communities in beach clean-ups and recycling programs can help reduce the amount of plastic waste that enters the ocean (Callos, 2019). Educational programs and campaigns can also help raise awareness about the impact of marine plastics on the environment and encourage individuals to reduce their plastic consumption and properly dispose of plastic waste (Liu et al, 2023).…”
Section: Control Measure Strategies To Mitigate Marine Plasticsmentioning
confidence: 99%